Effects of obesity reduction on transient elastography–based parameters in pediatric non-alcoholic fatty liver disease. Issue 5 (September 2020) - Isoura, Yoshiharu; Cho, Yuki; Fujimoto, Hiroki; Hamazaki, Takashi; Tokuhara, Daisuke
Highlights: Weight reduction ameliorates both hepatic fat deposition and liver stiffness associated with NAFLD in obese children. Reduction of CAP was positively correlated with baseline CAP value and reduction of body weight. Weight control by short-term hospital admission is an alternative effective approach to obtain an improvement of NAFLD. After weight reduction, we may non-invasively assess its effect on degrees of NAFLD by transient elastography more exactly. Abstract: Aim: To clarify the effects of obesity reduction on non-alcoholic fatty liver disease (NAFLD) in obese children. Methods: Twenty-six obese pediatric NAFLD patients (median age, 13.0 years; range, 6.4–16.6 years), who underwent obesity management supported by regular hospital visits and/or hospital admission, were studied to explore how reductions in weight and body mass index (BMI) percentile affected two transient elastography–based parameters: controlled attenuation parameter (CAP) and liver stiffness (LS), which reflect the degree of hepatic fat deposition and liver fibrosis, respectively. Results: Univariate analysis revealed that CAP reduction was correlated positively with baseline CAP and reductions in weight and BMI percentile ( r = 0.320–0.525), whereas LS reduction was correlated positively with baseline LS and reductions in weight, BMI percentile, aspartate transaminase, and alanine aminotransferase ( r = 0.385–0.625). Multivariate analysis revealed that baseline CAP and reduction in weight were significantly associated with CAP reduction, whereas reduction in weight and alanine aminotransferase were significantly associated with LS reduction. Short-term weight control by hospital admission (24.9 ± 9.5 days) provided significantly higher reductions in weight and BMI percentile (both P < 0.001) and was associated with reductions of CAP and LS ( P = 0.04 and 0.01) compared with regular hospital visit-supported self-directed weight management (0.9 ± 0.8 years). Conclusions: Weight reduction in obese pediatric NAFLD patients resulted in reduced hepatic fat deposition and liver stiffness. Weight control by short-term hospital admission is an alternative approach to regular hospital visit-supported self-directed weight management in NAFLD patients who fail to reduce obesity.